109 Developing an on-line toolkit to support end of life care. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - England, Ruth; Shreeve, Phil
Abstract : Background: When the Liverpool Care Pathway was removed, a range of materials and guidance required review; furthermore, revised practice needed a platform in order to be shared. We decided that our new approach to care might be supported by a novel on-line resource. Methods: A suite of tools that could be used by different providers across Derbyshire at different stages in a patient's end of life journey were collected together. Initially, these documents were held on a webpage hosted by a local community healthcare provider. An accompanying webpage contained details of upcoming educational events and contacts. In the first 6 months the pages were used regularly. However, feedback stated they were not easily accessible to all staff and were clumsy to use. Funding was obtained to build a more 'user friendly' resource. An improved platform (www.derbyshire.eolcare.uk) was launched in October 2015. As well as a library of resources, the website offers users the option to create an individualised learning portfolio. This can be linked to existing accredited resources (eELCA) as well as signposting to local face to face educational events. Results: In the period 1.10.2016–30.9.2017, 9862 sessions were conducted on our website, by 5842 users. The average number of pages viewed per session was 3.6 with an average session duration being 3'34 'More than 50% of users in this period were new to the website and our low bounce rate suggests that people who came to us found what they were looking for. The most popular resource was symptom management guidance. Conclusions: This novel website is a well-used platform for a suite of resources, as well a means of educational support for those engaging in end of life care.